Changes in texture, rheology and volatile compounds of golden pomfret sticks inoculated with Shewanella baltica during spoilage. (15th March 2023) - Lou, Xiaowei; Wen, Xiaokang; Chen, Leijian; Shu, Weichen; Wang, Yue; Hoang, Tung Thanh; Yang, Hongshun
Graphical abstract: Highlights: Effect of S. baltica on texture and flavour of golden pomfret were investigated. S. baltica decreased fish hardness, and the storage and loss moduli of proteins. MHC, MyBP-C and actin were degraded by S. baltica . S. baltica produced dimethyl sulfide, 2-methyl-butanal and 3-methyl-butanal. Abstract: Shewanella baltica has a high spoilage ability to decompose nutrients in fish. To investigate the role of S. baltica in fish protein and flavour during spoilage, the texture, rheology, protein patterns and volatile compounds of golden pomfret inoculated with S. baltica during 10-day storage were tested. During storage, S. baltica reduced the hardness of fish sticks by 29.73–49.24 %. Compared to the control (G0 ′: 20.27 ± 2.15 kPa), inoculated samples showed lower moduli (G0 ′: 16.71 ± 0.82–17.50 ± 1.80 kPa). Their myosin heavy chains, myosin-binding protein C and actin were decomposed into smaller proteins, which was validated by the lower intensities of molecules with Mw 160–176 kDa. Furthermore, S. baltica generated volatile spoilage markers, including dimethyl sulfide, 2-methyl-butanal and 3-methyl-butanal. This study reveals the mechanism of fish texture and flavour changes induced by S. baltica, and provides insights into controlling bacterial spoilage of seafood.